Extreme power saving directional MAC protocol in IEEE 802.11ah networks. Issue 4 (1st July 2020) - Ngo, Quynh T.; Dang, Duc N.M.; Le‐Trung, Quan
Abstract : In this study, a novel directional medium access control scheme with an extreme power saving mechanism is developed for traffic indication map stations in the IEEE 802.11ah networks. To improve the aggregate throughput, stations are managed based on their geographical locations in combination with the employment of directional operation mode on the access point. In addition to the restricted access window mechanism used in the IEEE 802.11ah standard for power saving, an adaptive transmission power scheme is proposed for uplink transmission to leverage the power‐saving efficiency. With the proposed access scheme, the network performance is significantly enhanced compared to the IEEE 802.11ah standard. The analytical models for throughput and energy consumption are formulated using Markov Chains under unsaturated conditions. The simulation results indicate the effectiveness of the proposed directional access scheme under various network scenarios.